Revenue and Tourist Reporting Application for the City of Pekanbaru - Nasution, Salhazan; Mulyadi, Ahmad (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2020)
Tourism service is a field that aims to introduce and promote marine and other tourism in a certain location especially in marketing field to attract tourists to visit that tourist destination. Culture and Tourism Service of Pekanbaru is one of the technical services which handles government business which is compulsory affairs in culture field and choice affairs in tourism field. The total of tourist visits must be reported to tourism office in each destination. To facilitate the reporting of the total of tourists then, a website and an android-based system are built. The system is developed using the CodeIgniter web framework with PHP and HTML programming language. The application is developed using Android Studio and Java Development Kit. Research result on Progress and recapitulation reports system of the revenue and total Tourists in Pekanbaru City based on web and android which ease to conduct report on total of tourist visits. Usability Testing of this system using the USE Questionnaire and Likert Scale.